Records and altitudinal assessment of Amblyomma aureolatum and Amblyomma ovale (Acari: Ixodidae) in the State of Rio de Janeiro, southeast Brazil - Faccini, João L. H. (2022)
Universidade Federal Rural do Rio de Janeiro. Departamento de Parasitologia Animal. Seropédica, RJ, Brasil.